Search for slow magnetic monopoles with the NOvA detector on the surface (2020)
We report a search for a magnetic monopole component of the cosmic-ray flux in a 95-day exposure of the NOvA experiment’s Far Detector, a 14 kt segmented liquid scintillator detector designed primarily to observe GeV-scale electron neutrinos. No events consistent with monopoles were observed, setting an upper limit on the flux of 2 ×10−14 cm−2 s −1 sr−1 at 90% C.L. for monopole speed 6 × 10−4 < β < 5 × 10−3 and mass greater than 5 × 108 GeV. Because of NOvA’s small overburden of 3 meters-water equivalent, this constraint covers a previously unexplored low-mass region.